The Implementation of Endoscopic Ultrasound Facilitates for Diagnosis of IgG4 Autoimmune Pancreatitis - Voidila, Sofia; Sideris, Panagiotis; Letsas, Constantinos; Anastasopoulos, Elias; Oikonomou, Ioanna (Research Highlights in Disease and Health Research Vol. 6, 2023)
The present case study highlights the role of endoscopic ultrasound in diagnosis in painless obstructive jaundice caused by IgG4 autoimmune pancreatitis. A female patient, 60-years-old, was admitted to the emergency department with painless jaundice. The patient did not have any history of alcohol consumption, drug abuse, or previous liver and biliary or hematologic diseases. This case highlights the rarity of AIP as a possible cause of obstructive jaundice and the challenging to establish role of endoscopic ultrasound (EUS) in the final diagnosis. According to diagnostic criteria, we combined the results from serologic, imaging and histological features (specifically lgG4 levels, computed tomography, magnetic resonance imaging/magnetic resonance cholangiopancreatography and EUS) with cytological results, leading to a final diagnosis. The prognosis of AIP is generally good and complications rare. Our patient remains free from symptoms three years after diagnosis with a successful treatment of relapse. The response of patient to corticosteroids was impressive, confirming the diagnosis, leading to complete remission of the disease. Whilst diagnosis of AIP is challenging, the application of diagnostic criteria can lead to correct diagnosis. Therapy is corticosteroid based, with very satisfying outcomes.